NARCOTICS CONTROL BY THE DIRECTORATE GENERAL OF CUSTOMS AND EXCISE AT THE BATAM TYPE B CUSTOMS AND EXCISE MAIN SERVICE OFFICE - Tri Lukita Adi; Bachtiar Simatupang; Erni Yanti; Soerya Respationo (RADJA PUBLIKA, 2023)
Narcotics control at the Batam Type B Customs and Excise Main Service Office with patrol activities, stopping, deterring, sealing and inspecting people, facilities and goods transported across the customs area. Law enforcement includes actions to stop, deter, examine and research files and extract more in-depth information about the perpetrator, then hand it over to National Narcotics Agency/Police investigators. Establishment of the Batam Intelligence and Analyzing Center (BIAWAC), as well as implementation of Cyber ​​Crawling techniques with Data Scraping.